Customer’s Loyalty Parameters of Sikorsky S76 Chartered Helicopter - Arsya Nadira Syafiudin; Ika Utami Yulihapsari; Azmieti Kurnia Sinta; Salahudin Rafi; Jermanto Setia Kurniawan; Theresye Yoanyta Octora (Jurnal Manajemen Transportasi & Logistik (JMTRANSLOG), 2023)
The study aims to determine the impact of the maintenance department and supporting facilities of PT. Pelita Air Service 2020 loyalty’s performance based on its customer’s satisfaction. The sample of 150 respondents from PT. Pelita Air Service’s Sikorsky S76 chartered Helicopter customers were obtained using quantitative descriptive method and purposive sampling using Slovin formula. SEM path analysis method and Smart Partial Least were used to test the validity and reliability of the data. Based on the findings, the performance of the Sikorsky S76 Helicopter’s maintenance department and chartered support facilities has a direct positive and significant impact on customer’s satisfaction and loyalty. The satisfaction factor has a direct positive and significant impact on customer’s loyalty. The customer’s satisfaction affects the performance of the maintenance department and the supporting facilities of the Sikorsky S76 chartered Helicopter at PT. Pelita Air Service 2020.